Persepsi Komunitas Solo Hijabers Mengenai Konstruksi Citra Perempuan dalam Kontes Kecantikan - Rhesa Zuhriya Briyan Pratiwi; Eny Susilowati (ARISTO, 2020)
Beauty is a social construction, no exception on how beautiful concepts are raised in a beauty contest which is aired in media. Describing the image of women is inseparable from the social construction of concept of beauty. This research is to describe the perceptions of members of the Solo Hijabers community in interpreting the construction of women's images through beauty contest shows. By using a qualitative descriptive method, data collection is mainly carried out through in-depth interviews with research subjects of Solo Hijabers community. In order to obtain the data validity, this research uses source triangulation and interactive data analysis. Results of this research explained that the meaning of Solo Hijabers on women's image was stated differently. However, the beauty image of women interpreted is basically complex—both physical and personality—so that a beauty contest cannot be used as the main standard. The media can describe a number of images of women, but in its construction, media actually presents women as objects of commodities that appear to be obscured.